Pengaruh Manajemen Aset Terhadap Tingkat Optimalitas Aset Tetap (Tanah) Pemerintah Provinsi Jambi - Wawan Devis Wahyu (Universitas Negeri Surabaya, 2022)
The purpose of this study was to analyze the effect of fixed asset management (land) belonging to the Jambi Provincial Government. A total of 46 sample respondents were taken in this study using purposive sampling method. Asset inventory, asset legal audit, asset valuation, and asset monitoring and control are the variables used in this study. From the results of the analysis using the Multiple Linear Regression test tool, it shows the results of an individual test that it is proven that asset inventory has a positive and significant effect on the optimality of fixed assets (land) which means that it matches the hypothesis, but individually legal audits of asset valuation, as well as asset monitoring and control not proven to have a positive and significant effect on the level of optimality of fixed assets (land) which means that it is not in accordance with the hypothesis, while the results simultaneously show that the four variables, namely asset inventory, asset legal audit, asset valuation, and asset monitoring and control, have a significant and positive effect. to the optimal level of fixed assets (land), the results are proven by the value of F-count > F-table.